Linear Differential Equations with Solutions of Finite Iterated p-Φ Order - Ghosh, Chinmay; Datta, Sanjib Kumar; Bandyopadhyay, Anirban; Mondal, Soumen (The Journal of the Indian Mathematical Society, 2023)
In this article, we have studied complex linear homogeneous differential equations whose coefficients are entire functions having finite iterated p − Φ order and the growth of its nontrivial solutions.